NEED TO FORM CREATIVE COMPETENCE IN EDUCATORS - Egamberdiyev, Oyatillokh Alisher ugli; Maxamadjonov, Jakhongir Zokirjon ugli; Sobirova, Azizaxon Maribjon kizi (Educational Research in Universal Sciences, 2022)
The article presents ideas about the need to develop creative competence in pedagogues.